(untitled) (Web of Teachers: Inderscience Research, 2024)
The importance of improving methodological training and professional development of primary school teachers as a scientific-pedagogical problem is studied in the article. It summarizes the opinions of foreign and local researchers. The principles, theoretical and pedagogical aspects of professional development of primary school teachers are scientifically based.